Analysis of the Development of Religious and Moral Values in Children Aged 5-6 Years in PAUD Penabur Filadelfia Suka Dame Kutalimbaru District - Febi Selviani; Dorlince Simatupang (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research was conducted with the aim of knowing the developmental achievements of children's religious and moral values ​​at PAUD Penabur Filadelfia, the RPPH used by teachers to develop children's religious and moral values ​​and activities for developing religious and moral values ​​for children aged 5-6 years at PAUD Penabur Filadelfia Suka Dame Kutalimbaru District. This research is a descriptive qualitative research, and the data were analyzed using the Miles and Huberman technique, namely data collection, data reduction, data presentation and drawing conclusions. The results of the study prove that the achievement of the development of religious and moral values ​​of children in PAUD Penabur Filadelfia, most of the children have developed as expected in each indicator. Furthermore, the RPPH used by teachers at PAUD Penabur Filadelfia to develop children's religious and moral values ​​is quite complete, the PAUD Penabur Filadelfia teacher has been able to design RPPH properly and carry out learning activities in accordance with the developmental needs of children. Meanwhile, activities for developing religious and moral values ​​for children at PAUD Penabur Filadelfia consist of routine and programmed activities, integrated activities and special activities. Overall the teacher has carried out each activity well.